Deborah Pacini-Hernandez. Oye Como Va! Hybridity and Identity in Latino Popular Music - Calle, Simón (Current Musicology, 2011)
Despite the fact that the number of Latin American immigrants and persons of Latin decent in the United States has increased significantly in the last two decades, mainstream mass media and academia have often neglected the contributions of these communities to US popular culture, and especially to music. However, this trend seems to be changing in the past few years with the production of documentaries such as Latin Music USA (aired in 2009 on PBS), and the increasing publication of academic books that focus on specific music genres performed by Latinos (eg. Ragland 2009; Rivera, et al. 2009; Washburne 2008). With Oye Como Va!, Deborah Pacini-Hernandez contributes to the literature on Latino music and culture by blending sophisticated and comprehensive socio-cultural analysis of several music genres performed by Latinos such as rock, salsa, meregue, reggaeton, hiphop, and cumbia, along with basic histories of the genres and a tracing of their multiple interconnections. As an anthropologist, Pacini-Hernandez’s is primarily concerned with the question of Latino identity formation through popular music performance, recording, marketing, and reception. Since most of this music emerge from the crossroads of transnational flows of music and people from different nations in the Caribbean and the Americas, she provides a comparative and connective history of national and transnational music genres and their transformation in relation to cultural, social, economical, and political processes primarily within the United States, and also the Americas. Thus, the book’s main interest groups would be those within academia, especially anthropologist, ethnomusicologist, and cultural studies scholars, interested in American and Latino Studies, and those who study mass-mediated popular music in the United States; yet, it is accessible for the general reader.